Accelerated hypofractionated radiation therapy compared to conventionally fractionated radiation therapy for the treatment of inoperable non-small cell lung cancer - Amini Arya; Lin Steven H; Wei Caimiao; Allen Pamela; Cox James D; Komaki Ritsuko (Radiation Oncology, 2012)
Abstract Background While conventionally fractionated radiation therapy alone is an acceptable option for poor prognostic patients with unresectable stage III NSCLC, we hypothesized that accelerated hypofractionated radiotherapy will have similar efficacy without increasing toxicity. Methods This is a retrospective analysis of 300 patients diagnosed with stage III NSCLC treated between 1993 and 2009. Patients included in the study were medically or surgically inoperable, were free of metastatic disease at initial workup and did not receive concurrent chemotherapy. Patients were categorized into three groups. Group 1 received 45 Gy in 15 fractions over 3 weeks (Accelerated Radiotherapy (ACRT)) while group 2 received 60-63 Gy (Standard Radiation Therapy 1 (STRT1)) and group 3 received > 63 Gy (Standard Radiation Therapy (STRT2)). Results There were 119 (39.7%) patients in the ACRT group, 90 (30.0%) in STRT1 and 91 (30.3%) in STRT2. More patients in the ACRT group had KPS ≤ 60 (p < 0.001), more commonly presented with weight loss > 5% (p = 0.002), and had stage 3B disease (p < 0.001). After adjusting for clinical variables, there were no differences in the radiation groups in terms of the patterns of local or distant tumor control or overall survival. Some benefit in relapse free survival was seen in the STRT1 group as compared to ACRT (HR = 0.65, p = 0.011). Acute toxicity profiles in the ACRT were significantly lower for grade ≥ 2 radiation dermatitis (p = 0.002), nausea/vomiting (p = 0.022), and weight loss during treatment (p = 0.020). Conclusions Despite the limitations of a retrospective analysis, our experience of accelerated hypofractionated radiation therapy with 45 Gy in 15 fractions appears to be an acceptable treatment option for poor performance status patients with stage III inoperable tumors. Such a treatment regimen (or higher doses in 15 fractions) should be prospectively evaluated using modern radiation technologies with the addition of sequential high dose chemotherapy in stage III NSCLC.